2013
DOI: 10.3368/le.89.2.211
|View full text |Cite
|
Sign up to set email alerts
|

What Do Property Values Really Tell Us? A Hedonic Study of Underground Storage Tanks

Abstract: Hedonic property value models are widely used, but are susceptible to omitted variable bias and potentially invalid conjectures regarding the assumed measure of environmental quality. This paper focuses on an application where both are of particular concern: leaking underground storage tanks. I estimate a hedonic model using quasi-experimental and spatial econometric techniques. Similar to previous studies, I examine how house prices vary with distance to the disamenity. This approach yields little evidence th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 41 publications
(42 reference statements)
3
25
0
Order By: Relevance
“…The effect of the New York moratorium is to change expectations, whereas the results of the proximity analysis using only Pennsylvania properties support the idea of rational expectations because no price changes occur once drilling commences. This work also complements hedonic studies that show new information can cause capitalization of disamenities, even when levels of dis-amenities do not change (e.g., Pope, 2008;Guignet, 2013).…”
Section: Introductionmentioning
confidence: 74%
“…The effect of the New York moratorium is to change expectations, whereas the results of the proximity analysis using only Pennsylvania properties support the idea of rational expectations because no price changes occur once drilling commences. This work also complements hedonic studies that show new information can cause capitalization of disamenities, even when levels of dis-amenities do not change (e.g., Pope, 2008;Guignet, 2013).…”
Section: Introductionmentioning
confidence: 74%
“…Given the seeming importance of households' awareness of the disamenity and the information aiding in their formation of perceived risks, we next examine how households being explicitly informed may impact the annual probability of a sale. In a previous hedonic study of these data, Guignet (2013) found that transaction prices were 11% lower among homes where the private well was tested. At these homes households were most at risk to exposure, and were formally notified (ii) whether the test results revealed contamination levels above zero, or above the regulatory standards in Maryland.…”
Section: Resultsmentioning
confidence: 89%
“…All the parcel, house structure, and locational covariates presented in Table 1 are included on the right-hand side of the regression models, as are year fixed effects to control for broader housing market trends, and dummy variables denoting the duration period of the housing spell. 7 of a primary exposure pathway (e.g., Guignet, 2012Guignet, , 2013Muehlenbachs et al, 2015), in this case private groundwater wells being the source of potable water. 1.B is estimated on the full sample by interacting all treatment-related variables with dummy variables denoting two mutually exclusive groups-one denoting homes that rely on private wells to obtain water, and the other denoting homes connected to the public water system.…”
Section: Resultsmentioning
confidence: 99%
“…A vast body of research has examined the housing price effects of locally undesirable land uses, such as hog operations [Palmquist et al, 1997], underground storage tanks [Guignet, 2012], and power plants [Davis, 2011] to name a few. These estimates are then used to measure the disamenity value of the land use (or willingness-to-pay to avoid it).…”
Section: Market Valuationmentioning
confidence: 99%